Faktor Budaya Organisasi, Kepemimpinan Transformasional dan Kompensasi Berpengaruh Terhadap Kinerja Karyawan (Studi Pada Kantor Telkom Cabang Banjarmasin) - Mahfuzil Anwar (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2018)
This research propose to examine the effect organization culture, tranformational leadership, and compensation, on employee performance. Ninety eight respondents from PT Telkom Cabang Banjamasin, completed 65 itemsself-reported measures. The data collected survey method and questionares distributed to respondent. The statistic method used was Multiple Regression. As expected, result indicated that tranformational leadership and compensation has a positive effects on employee performance, while organization culture didnt have effect on employee performance, its mean that The Telkom Way 135 which made since 2003 couldnt employee perform, because before it telkom had strong organization culture. Furthermore, results show that tranformational leadership have a stronger effect on employee performance than compensation.